(3GdEceGds - (3Ydj Hf gHI Gddg Hf Ydj Hf LYaQ, CHh fUQ, SYO Gdedc, GHf eGchdG,J (B475 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ , hChd GdehLhO efg (B_ (3CKfGA MQa GdYjf (B_ (3HGH YJQ s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg (B- (3CKfGA MQa GdjGA(B- (3HGH jfGQ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B257s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdJGQjNs